2021
DOI: 10.1016/j.ijchp.2021.100224
|View full text |Cite
|
Sign up to set email alerts
|

Mental health of people with distorted body weight perception using medicinal remedies: A representative study

Abstract: Background/Objective We aimed to examine the prevalence of distorted body weight perception (BWP) and the choice of weight control strategies to investigate the associations between the psychological features and the different strategies for controlling body weight. Method: We used a representative nationwide 39-item survey to randomly select 1,000 participants. The extrapolated number (eN) to the whole national population was also reported. Self-BWP, weight control strategies, and obesity-related p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Especially for females, the well-being scores for the group with obesity were significantly lower than for that the other groups. These results are consistent with those of a previous study, which reported that males who perceived themselves as underweight had low body satisfaction and self-esteem [ 18 ], and women who overestimated their weight reported the most negative psychological conditions including anxiety, self-esteem, body satisfaction, quality of life, and eating attitudes [ 30 ]. However, although the interaction effect between OBP and gender on stress perception was statistically significant, both men and women showed very similar results for stress perception; the scores were highest for the group with obesity and decreased in order for the groups with underweight and healthy weight.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Especially for females, the well-being scores for the group with obesity were significantly lower than for that the other groups. These results are consistent with those of a previous study, which reported that males who perceived themselves as underweight had low body satisfaction and self-esteem [ 18 ], and women who overestimated their weight reported the most negative psychological conditions including anxiety, self-esteem, body satisfaction, quality of life, and eating attitudes [ 30 ]. However, although the interaction effect between OBP and gender on stress perception was statistically significant, both men and women showed very similar results for stress perception; the scores were highest for the group with obesity and decreased in order for the groups with underweight and healthy weight.…”
Section: Discussionsupporting
confidence: 92%
“…Distorted body perception is related to body dissatisfaction and attempting unhealthy weight control strategies, which lead to body dysmorphic disorder, health-obsessive behaviors, low quality of life, and eating disorders [ 27 29 ]. Also, distorted body perception and weight control strategies are related to the prevalence of psychological problems, as people with inaccurate perceptions of their body shape who use medical procedures for weight control could be at a higher risk of psychological disorders [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to Monteiro et al (2022), self-esteem is a component of self-concept. Self-esteem is related to self-confidence and better mental health (Kim et al, 2021). Besides, individuals with higher self-esteem can exert self-control and recognise when to quit (Baumeister et al, 2003).…”
Section: Self-esteem and Mental Toughnessmentioning
confidence: 99%